The Independent Learning Curriculum: Teachers’ Perspectives on Challenges and Expectations at SMP Negeri 1 Tuhemberua - Cinthika Joe Apriani Harefa (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The Independent Learning Curriculum (KMB) is a new curriculum that was established by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia in 2022. This study was conducted at SMP Negeri 1 Tuhemberua with the aim of examining teachers’ perspectives on the challenges and expectations related to KMB. This study used a qualitative method with a case study approach. Data were collected through in-depth interviews with 5 teachers. The result of the study showed that teachers faced various challenges in implementing KMB at SMP Negeri 1 Tuhemberua, including: (1) lack of teacher understanding of KMB, (2) limited time, (3) lack of resources to support KMB learning, and (4) students were unable to follow the learning flow, so the learning objectives given by the teacher could not be achieved to the maximum. Despite these challenges, teachers also had high hopes for KMB at SMP Negeri 1 Tuhemberua, namely: (1) to improve the quality of learning, (2) to develop potential students optimally, and (3) to create a more enjoyable learning experience. This study contributes to the development of knowledge in the field of education by providing insights into the challenges and expectations of teachers related to KMB at SMP Negeri 1 Tuhemberua. This study can also be a reference for the government in implementing KMB optimally in various regions.